DNA Barcoding of The Penang Hill Slipper Orchid (Paphiopedilum Barbatum) - Hassan, Khairun Ayuni Afiqah; Yap, Jing Wei (Enhanced Knowledge in Sciences and Technology, 2025)
Paphiopedilum is a genus of the slipper orchid from the subfamily Cypripedioideae. Penang Hill, Malaysia is home to a distinct variety of Paphiopedilum barbatum (Paphiopedilum Penang Hill) which has been almost extirpated from its native range. Although there is interest in breeding and reintroducing Paphiopedilum Penang Hill from individuals in Penang Botanic Garden, it is vital to ensure the origin of these plants. In this study, DNA barcoding was used to confirm the taxonomic status of Paphiopedilum Penang Hill. Representative samples of these species were obtained by fresh field collections. PCR amplification was attempted using primers for two DNA barcoding regions: maturase K (matK) and the internal transcribed spacer II (ITS2) nuclear region. Both of the regions were successfully amplified except for one sample from Penang Botanic Garden. Maximum likelihood and maximum parsimony trees were constructed on those samples and other outgroup sequences from GenBank. The phylogenetic analysis revealed that while both regions were successfully amplified, the bootstrap values for the phylogenetic trees were low, indicating weak statistical support for genetic distinction between the two populations. The ITS2 region results further suggested a close genetic relationship between the Penang Hill and Botanic Garden samples.